Facilitating Open Access to Information: A Community Approach to Open Education and Open Textbooks. Issue 1 (18th October 2019) - Stagg, Adrian; Partridge, Helen
ABSTRACT : Access to information as a necessary precondition for human flourishing is recognized explicitly in the UNESCO Strategic Development Goals, and mirrored by the work of universities globally to reduce barriers to information, especially research outputs. Growing international attention has turned to learning and teaching resources, particularly textbooks as a key barrier to fully engaging with, and participating in, higher education. The affordances of open texts provide an alternative to commercially published and often exclusionary access practices; and empower educators and students in co‐creation and open sharing of information and knowledge. This paper examines the design of an ongoing institutional grants program predicated on a facilitated community learning approach for academic staff seeking to adopt, or adapt open textbooks into the curriculum as one mechanism to increase access to information. The participants' experiences and personal learning were captured through a series of semi‐structured interviews that inform the iterative design of the ongoing grants program that could be transferred to other institutions seeking to support educational change.